2016
DOI: 10.1016/j.jcrs.2015.11.044
|View full text |Cite
|
Sign up to set email alerts
|

Keratoconus correction using a new model of intrastromal corneal ring segments

Abstract: The ICRS provided topographic and visual improvement in keratoconus and post-LASIK keratectasia. Variance in surgical outcomes with manual versus femtosecond tunneling and the effect of different ring sizes are yet to be studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 16 publications
0
20
0
2
Order By: Relevance
“…Visual outcomes in our study are comparable or superior to all prior studies. Israel reported improved UCVA and CDVA from 0.02 to 0.06 to 0.16 and 0.32 respectively, and a reduction of spherical error from − 9.5 to − 0.5D [35]. Yousif and Said reported better visual and topographic outcomes with MyoRing and 320°rings compared symmetric ring segments.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Visual outcomes in our study are comparable or superior to all prior studies. Israel reported improved UCVA and CDVA from 0.02 to 0.06 to 0.16 and 0.32 respectively, and a reduction of spherical error from − 9.5 to − 0.5D [35]. Yousif and Said reported better visual and topographic outcomes with MyoRing and 320°rings compared symmetric ring segments.…”
Section: Discussionmentioning
confidence: 95%
“…e first study was conducted in Egypt by Israel and her colleagues who reported the outcomes for 4 types of rings: 160, 210, 320, and 355 [35]. After that, Yousif and Said compared 3 types of rings: 2 symmetric 160°ring segments, 320°rings, and MyoRing [34].…”
Section: Discussionmentioning
confidence: 99%
“…1). Removal of duplicates and use of the selection criteria reduced the number of articles reporting the evaluation of ICRS in keratoconus to 95 articles 8,1416,26…”
Section: Resultsmentioning
confidence: 99%
“…The reference point was a Sinskey hook marking the center of the pupil. Channel depth varied between 70% ( references 1416, 33, 35, 37, 48-54, 63, 65, 66, 70, 80, 82, 83, 87, 88, 90, 92, 95, 98, 99, 102, 103, 105, 108, 109, 111, 113, 114 ), 75% ( references 26, 27, 34, 39, 41, 42, 45, 58, 60, 64, 71, 79, 110 ), or 80% ( references 8, 29, 30, 32, 33, 43, 47, 5456, 59, 62, 6769, 72–…”
Section: Resultsmentioning
confidence: 99%
“…ICRS corrects corneal ectasia via shortening the cone length, causing corneal flattening to the periphery [ 127 ]. Improvements in the refractive power, topographic measurements, and optical quality have been reported postoperatively, with an increase in contact lens tolerability [ 127 129 ]. Complications, such as segment extrusion, segment migration, or shadow effects, have been found to be rare among patients [ 127 ].…”
Section: Histopathological Abnormalities In Kcmentioning
confidence: 99%